Encounters with Andrew Stewart - Hölscher, Tonio (Journal of Greek Archaeology, 2023)
Writing in memory of Andrew Stewart is an almost impossible task. For all who have ever met him he was, and still is, incomparably present, not only in his books and articles but as a person. Even using his official first name presupposes an inappropriate distance: he was and is ‘Andy’. His scientific thoughts and insights are not just dated texts on paper but ongoing provocative challenges in life, beyond libraries, classrooms and desks. Those who have once been confronted with them continue to have them in their minds and before their eyes. Yet all this was never achieved by translating ancient Greek culture light-heartedly into notions of present-time actuality and ‘identity‘. On the contrary: he transferred himself and his audiences deep into the world of antiquity - and not only through his enormous erudition but by an emphatic and vital immersion, with burning curiosity, into this foreign world with its inhabitants. This was a past, but in a way it was not yet over: he brought these people to life.